Analisis Konflik Norma dalam Hierarki Aturan Perpajakan di Indonesia yang Mengakibatkan Celah Korupsi - Rahel Pratama; Putra Batara Sakti Wiguna; Bayu Candra Dwi Wijaya Nuredi Putra; Talitha Dewi Yumna Nabila; Indah Wahyu Pratiwi (Fakultas Hukum, UPN Veteran Jawa Timur, 2025)
This study aims to identify conflicts of norms within tax statutory regulations in Indonesia, which are frequently perceived as containing grey areas that can be exploited for abuse of power, such as corruption commonly committed by corporations. These loopholes arise from the existence of two or more positive laws governing the same subject matter that contradict one another. This study employs a normative legal research method based on statutory regulations, court decisions, and legal literature. The author utilizes this approach to identify legal rules or principles that assist in resolving the legal issues under review. The findings indicate that the hierarchy of tax regulations creates significant legal uncertainty. This condition is often exploited by corporations through aggressive tax avoidance schemes. Keywords: Corruption; Taxation; Norm Conflict; Hierarchy